Peningkatan Kemampuan Lompat Jauh dengan Menggunakan Media Kardus Bekas Kelas V SDN 12 Pelerang Kecamatan Sukadana Kabupaten Kayong Utara - Firdaus, Rahmad; Porja Daryanto, Zusyah (Journal Sport Academy, 2023)
Sports activities for fifth grade elementary school students are not an abstract experience. Therefore, the use of used cardboard teaching aids is very important to make it easier for students to learn long jump practice. One of the alternative props that can be used in long jump practice is Used Cardboard. The purpose of this study was to find out how the use of Used Cardboard teaching aids can improve Long Jump abilities in fifth grade students at SDN 12 Pelerang Sukadana sub-district, North Kayong district. After carrying out classroom action research for 2 research cycles, in general it can be said that by using used cardboard (KB) teaching aids, the ability of students quantitatively in the form of long jump ability and qualitatively in the form of interest, attention, participation, and student achievement has increased.